Malignant lesions in the ventral prostate of alloxan-induced diabetic rats - Ribeiro, Daniele Lisboa; Marques, Silvio Fernando Guideti [UNESP]; Alberti, Sandra [UNESP]; Spadella, César Tadeu [UNESP]; Manzato, Antonio Jose [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Dizeyi, Nishtman; Abrahamsson, Per-Anders; Goes, Rejane Maira [UNESP] (Wiley-Blackwell, 2008)
The aim of this study was to evaluate the changes caused by chronic diabetes in the rat ventral prostate and to establish a correlation between diabetes and the development of prostatic lesions. Male rats received alloxan (42 mg/kg b.w.) to induce diabetes. Ninety days after diabetes diagnosis, animals were sacrificed and the ventral prostate was removed and prepared for general and immunohistochemical analyses. The total area showing different types of lesions was estimated. Diabetes led to a decrease in the body and prostatic weights, as well as in testosterone levels. The prostate morphology and stereology showed high variation in the diabetic group. Some animals had light changes; the great majority had an intense epithelial atrophy; and other rats showed premalignant and malignant lesions in the prostate. Such epithelial atrophy was, in some samples, combined with chronic inflammation, similar to proliferative inflammatory atrophy (PIA). The diabetic group also presented high incidence of prostatitis, adenocarcinoma and prostatic intra-epithelial neoplasia (PIN). Samples with adenocarcinoma had poorly differentiated acini with high levels of cellular proliferation and nuclear atypia. These lesions exhibited an invasive feature showing Bcl-2-positive cells and interruptions in the basement membrane. An association of PIA, PIN and adenocarcinoma was detected in one sample. Reduced androgen levels have a synergic effect to insulin dysfunction promoting negative effects in the rat prostate. Diabetic individuals had a high incidence of prostatitis, and this inflammation could stimulate the incidence of other forms of prostatic pathology.
Keywords: alloxan; Diabetes; Inflammation; intra-epithelial neoplasia; prostate atrophy